Roaming along the Stony Road: Absolute and Relative Priorities in Corporate Restructuring - Hupli, Tuomas (Helsingin yliopisto, 2026)
This chapter critically examines the Finnish corporate restructuring framework under the Restructuring of Enterprises Act, highlighting its unchanged state since Johanna Niemi’s 1995 doctoral thesis. A central concern is the protection afforded to shareholders of insolvent companies, while creditors bear the financial burdens through significant reductions to their claims. The chapter emphasises Niemi’s influential perspective that insolvency law ultimately affects human lives, not just financial transactions. It also explores the moral and legal implications of the order of priority in insolvency proceedings, which the EU leaves to individual Member States. The chapter discusses the limitations imposed by the Finnish Supreme Court’s ruling in KKO 2003:73, particularly regarding the application of the absolute priority rule (APR) in cross-class cram downs. It concludes by assessing the potential for future reform through ongoing legislative efforts, such as the debt-to-equity swap project, while acknowledging the enduring constraints of existing statutory law.
The Neutral Law? Essays in Honour of Johanna Niemi